2013
DOI: 10.1093/jxb/ert357
|View full text |Cite
|
Sign up to set email alerts
|

A chloroplast-targeted DnaJ protein contributes to maintenance of photosystem II under chilling stress

Abstract: A novel tomato chloroplast-targeted DnaJ protein, LeCDJ1 was found to contribute to the maintenance of photosystem II under chilling stress and this maintenance effect was, at least partially, independent of D1 protein synthesis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(114 citation statements)
references
References 59 publications
3
106
0
Order By: Relevance
“…In addition, a Dnaj-like (Spot 30) was also up-regulated under all Sb stress conditions. Dnaj proteins act as co-chaperones in protein homeostasis and protein complex stabilization under adverse conditions (Kong et al, 2014). Zhang et al (2000) showed that Dnaj-like proteincoding genes in Phaseolus vulgaris was up-regulated under Hg and Cd treatment, indicating that DnaJ-like protein may play a significant effect in maintaining cell structure and function under heavy metal stress.…”
Section: Stress Responsementioning
confidence: 99%
“…In addition, a Dnaj-like (Spot 30) was also up-regulated under all Sb stress conditions. Dnaj proteins act as co-chaperones in protein homeostasis and protein complex stabilization under adverse conditions (Kong et al, 2014). Zhang et al (2000) showed that Dnaj-like proteincoding genes in Phaseolus vulgaris was up-regulated under Hg and Cd treatment, indicating that DnaJ-like protein may play a significant effect in maintaining cell structure and function under heavy metal stress.…”
Section: Stress Responsementioning
confidence: 99%
“…At least 63 DnaJ genes were found in the tomato genome in the National Center for Biotechnology Information (NCBI). We isolated a tomato ( Lycopersicon esculentum ) chloroplast‐targeted type III DnaJ protein gene, LeCDJ1 , then constructed LeCDJ1 overexpressing plants, and proved its role in maintaining PSII under chilling stress in the previous study (Kong et al ). In the present study, we further proved that overexpression of LeCDJ1 increased heat tolerance by alleviating the photoinhibition of PSII and improving the activities of antioxidant enzymes in tomato chloroplast.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables produced in off-seasons are mainly grown in solar-energy greenhouses during winter-spring period when outside temperature is low. Low temperature is one of the major abiotic stresses limiting plant growth, development and productivity (Liu et al 2009(Liu et al , 2011Hu et al 2010;Kong et al 2013). Pepper (Capsicum annuum L.) is an important thermophilic crop and the optimal growth diurnal temperature is 28 and 18°C (day and night) (Allen and Ort 2001).…”
Section: Introductionmentioning
confidence: 99%